The results of tension band rotator cuff suture fixation of locked plating of displaced proximal humerus fractures. Issue 2 (February 2017) - Shukla, Dave R.; McAnany, Steven; Pean, Christian; Overley, Samuel; Lovy, Andrew; Parsons, Bradford O.
Abstract: Introduction: The purpose of this study was to assess 1-year outcomes of patients with displaced proximal humerus fractures who underwent treatment with locked plate fixation with rotator cuff suture augmentation. Methods: A total of 86 patients who had sustained 2, 3 and 4-part displaced proximal humerus fractures underwent locked plate fixation with multiple sutures placed in the cuff tendons. Clinical outcome variables included active forward elevation (AFE), active external rotation (AER), and Constant and American Shoulder and Elbow Surgeons (ASES) scores. Post-operative variables included the following complications: varus re-collapse, loss of fixation, osteonecrosis of the humeral head (AVN), screw cut out, hardware failure and infection. Results: Forty-one patients were available with minimum of 1-year follow-up. Mean AFE was 142 ± 17.0° and AER was 41 ± 13.0°. The overall complication rate was 14.6%, with osteonecrosis being the most common (12.2%). Of the 21 patients (51.2%) that initially had varus displacement, all but one maintained anatomic reduction and fixation. Mean ASES score was 78.2 ± 20.0 and average Constant score was 72.7 ± 17.6. Bivariate analyses demonstrated that pre-operative medial comminution (p = 0.297) or varus collapse (p = 0.95) were not associated with an increased likelihood of sustaining a complication. Conclusions: Follow-up of patients in this series demonstrated a low overall complication rate and excellent functional outcomes. We believe suture augmentation of the rotator cuff can counteract varus forces on proximal humerus fractures fixed with locked plates, and should be performed routinely in displaced 2, 3 and 4 part fractures.